2001
DOI: 10.1139/z01-035
|View full text |Cite
|
Sign up to set email alerts
|

Test of character displacement in urban populations of Apodemus sylvaticus

Abstract: We studied the wood mouse, Apodemus sylvaticus, inhabiting parks, cemeteries, suburban woods, and other green areas in the city of Prague. To assess the character displacement and (or) release hypothesis we compared seven samples from local populations occurring sympatrically with Apodemus flavicollis with 10 samples from those localities in which A. flavicollis has never been recorded. The analysis included 1410 specimens of A. sylvaticus collected during the years 1980–1990. Seventeen skull and body characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Furthermore, genetic analyses pointed to a low divergence of the lineages (maximum 1.6% genetic differentiation; Table 2). Cases of morphological differentiation in an even shorter time span are known, but they usually correspond to peculiar conditions such as small, isolated populations in insular conditions (Renaud & Millien, 2001) or fragmented populations as a result of anthropization (Mikulová & Frynta, 2001). The context of divergence between bank vole lineages is very different, as they came into contact regularly during interglacial periods, allowing for significant gene flow between large populations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, genetic analyses pointed to a low divergence of the lineages (maximum 1.6% genetic differentiation; Table 2). Cases of morphological differentiation in an even shorter time span are known, but they usually correspond to peculiar conditions such as small, isolated populations in insular conditions (Renaud & Millien, 2001) or fragmented populations as a result of anthropization (Mikulová & Frynta, 2001). The context of divergence between bank vole lineages is very different, as they came into contact regularly during interglacial periods, allowing for significant gene flow between large populations.…”
Section: Discussionmentioning
confidence: 99%
“…Changes (probably temporal) in body size among populations of A. sylvaticus were reported in other studies. For example, Mikulová and Frynta (2001) found slight but statistically significant differences between samples from localities in Prague city Mar. Dec. Fig.…”
Section: Discussionmentioning
confidence: 90%
“…These two patterns are likely not independent, as it can be suggested that the absence of competition between these two closely related and ecologically similar rodents is due to a too scarce population density of the two Apodemus that therefore do not exploit heavily the available spatial and food resources (e.g., Vandermeer 1975;Aguiar et al 2001;Begon et al 2006). Indeed, it is well demonstrated that these species do actually compete in other areas of their range where their respective population density is higher (e.g., Mikulová and Frynta 2001;Montgomery 2004Montgomery , 2008, as well as in other Apodemus species (Sekijima and Sone 2006). Concerning pattern (i), it should be stated that the low population density of both rodents was also confirmed by the fact that usual rodent predators as Strigiformes (Capizzi and Luiselli 1995) do forage for over 90% on arthropods at the study areas (Strix aluco and Tyto alba being the studied species; Fanfani et al 2001).…”
Section: Discussionmentioning
confidence: 99%